IMPACT OF COVID-19 ON SECONDARY EDUCATION IN INDIA - DUE TO VIRTUAL LEARNING - Dr. Poonam Beniwal , Dr. Anita Beniwal and Rashi Solanki, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The Covid-19 Pandemic created many challenges in front of us such as continuing the teaching- learning process when students and teachers could not present physically in the school. In order to maintain educational continuity in absence of face-to-face classes, we need to introduce a suitable online learning mode. Initially, the educators and the students were quite confused about online learning, but later all teachers and students adopted technology and were inspired to engage more technology dependent to tackle the emergence of such a pandemic. During Covid-19 lockdown, people are engaged in different activities like gardening, cooking and providing education through online platforms due to lack of face-to-face interaction. To avoid such problems and challenges in the future related to Covid-19, government as well as private players must come together in the education system to solve all the problems. As a government, policy can be made for students as well as for teachers to gain knowledge about the digital world and make education better.